Efficient Ammonia Synthesis from Nitrate Catalyzed by Au/Cu with Enhanced Adsorption Ability. Issue 4 (17th January 2023) - Bi, Bo; Dong, An-Qi; Shi, Miao-Miao; Sun, Xue-Feng; Li, Hong-Rui; Kang, Xia; Gao, Rui; Meng, Zhe; Chen, Ze-Yu; Xu, Tong-Wen; Yan, Jun-Min; Jiang, Qing
Abstract : The traditional method for synthesizing NH3 is the Haber–Bosch process which results in high‐fuel consumption and environmental pollution. Therefore, ecofriendly electrochemical synthesis of NH3 through nitrate (NO3 − ) reduction is a good choice. Herein, an integral Au/Cu electrode to catalyze NO3 − reduction to NH3 is introduced. The catalyst exhibits not only the highest NH3 yield rate (73.4 mg h −1  cm −2 ) up to now but also a very high Faradaic efficiency of 98.02% at −0.7 V at room temperature. It is commonly believed that the transformation of NO3 − to nitrite (NO2 − ) is an obstacle to the NH3 generation from NO3 − reduction. Surprisingly, unlike most of the other catalysts, Au/Cu exhibits better activity for NO3 − reduction than that for NO2 − reduction. Based on the detailed experimental and density functional theory calculations, the excellent performance of Au/Cu for selective NO3 − reduction lies in the enhanced adsorption capabilities of Au/Cu to NO3 − in the alkaline environment and the lower energy barriers of the electrochemical reduction reaction. Abstract : An integral Au/Cu foam electrode realizes the high NH3 yield rate (73.4 mg h −1  cm −2 and Faradaic efficiency (98.02%) from NO3 − electroreduction. The small addition of Au can induce structural relaxation and electron transfer at the interface, thus increasing the adsorption ability of Au/Cu, while displaying a superior performance for electrochemical NO3− reduction reaction (eNO3 RR) than that for eNO2 RR.